Simulation-Based Education in Undergraduate Nursing Pharmacology: A Systematic Review of Modalities, Effectiveness, and Design Quality - Massoud, Maria; McKeaveney, Clare; Alqhtani, Samirh Said; McCloy, Oonagh; Rogers, Katherine (British Journal of Healthcare and Medical Research, 2026)
Simulation-based learning is increasingly used in healthcare education; however, limited evidence exists on how it is specifically applied to support undergraduate nursing students in pharmacology. This systematic review aimed to examine the types of simulation modalities used to enhance pharmacology education, evaluate their effectiveness in improving students’ medication management, and assess the quality of existing studies. Systematic searches were conducted across seven databases, including Embase, CINAHL, Web of Science, PubMed, and Medline. Of the 3,060 records identified, 127 full-text articles were assessed for eligibility, and 51 studies met the inclusion criteria. Simulation modalities consistently improved pharmacology-related learning outcomes. Studies that incorporated structured pre-briefing, validated assessment instruments, and comprehensive debriefing protocols demonstrated the strongest statistical effects. However, students’ perceived self-efficacy in pharmacology was rarely examined, indicating an important gap in the current literature. Overall, effectiveness appeared to be influenced less by the level of simulation fidelity and more by the alignment between the simulation modality, learning objectives, student needs, and educational context. Adherence to best-practice standards recommended by the International Nursing Association for Clinical Simulation and Learning also appeared to strengthen learning outcomes. Simulation-based pharmacology education shows promise for improving medication competence among undergraduate nursing students, although further research is needed to evaluate self-efficacy outcomes and strengthen methodological rigour.